Grounding Detection Circuit Common-mode Voltageof Electric Locomotive Traction Main Circuit - NI Dacheng; YING Ting; ZHANG Yu (机车电传动)
The misinformation come up because of interference during operation of grounding detection for locomotive tractionmain circuit. The main circuit of locomotive traction system was introduced as well as the principles of grounding detection, and the effecton voltage of grounding detection loop caused by common mode interference in main circuits was analyzed. On the basis of the contentabove, the effective method of common mode interference suppression in grounding detection circuit loop was provided. In addition, thecorrectness of analysis was verified by simulation test and proved in experiments.